Faktor Faktor yang Mempengaruhi Terjadinya Hipertensi pada Ibu Hamil di Puskesmas Peureulak Aceh Timur Tahun 2024 - Isnoviliana Isnoviliana; Ester Simanullang; Rasmi Manullang (Inovasi Kesehatan Global, 2024)
Hypertension in pregnancy is hypertension that occurs when blood pressure is first detected in a mother who is known to have normal blood pressure but after 20 weeks of gestation who does not have significant urine protein and other characteristics of preecamsia. Then, data was obtained from the Health Profile of North Sumatra Province. The aim of this research was to analyze the factors that influence the occurrence of hypertension in pregnant women at the Peureulak Community Health Center. This research was quantitative with a case control research design. The population for conducting this research was all pregnant women registered in the register book at the Peureulak Community Health Center in 2023 In this study, a total sampling technique was used, namely all pregnant women recorded in the Peureulak Health Center's medical records in 2023. Population. This analysis requires several stages, namely: analysis of proportions or percentages, analysis of statistical test results and analysis of the close relationship between two variables. Bivariate analysis was carried out on two variables that were thought to be related or correlated. The conclusion from the results obtained was 0.000, where the results showed <0.05 that there was a significant relationship between parity and the incidence of hypertension.